Innovation behavior of Salvadoran food & beverage industry firms - Elías Humberto Peraza Castaneda; Guillermo Aleixandre Mendizábal (Revista Finanzas y Política Económica, 2021)
This paper presents a quantitative analysis about the external and internal determinants that affects the innovation dynamics of a low-tech sector in a less developed economy, the food & beverage (F&B) industry in El Salvador. The empirical framework relies on a multivariate probit analysis applied to data from the 1st National Innovation Survey 2013 of El Salvador. The results are useful to understand the specificities of low-tech sectoral systems of innovation in a less developed economy, the role that science, technology and innovation public policies can play in the Salvadoran agro-food innovation system and the managerial implications of external and internal innovation determinants in the case of Salvadoran F&B industry firms.